Analisis Yuridis Hadhanah Dan Kewajiban Orang Tua Dalam Praktik Daycare Perspektif Hukum Islam Dan Hukum Positif Di Indonesia - Jamil, Reforman; Yoki Pradikta, Hervin; Santoso, Rudi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Modern social developments have led to the increasing use of daycare services as an alternative form of childcare, particularly among dual-income families. This phenomenon raises juridical issues concerning the position of hadhanah (child custody in Islamic law) and the limits of parental responsibility when certain caregiving functions are delegated to childcare institutions. This study aims to analyze daycare practices from the perspectives of Islamic law and Indonesian positive law, as well as to examine their relevance to the concept of hadhanah and parental obligations. This research employs a qualitative method with a normative juridical approach, encompassing the statute approach, conceptual approach, and comparative approach. Data were collected through library research, including statutory regulations, classical fiqh literature, scholarly journals, and relevant court decisions.The findings indicate that Islamic law permits the involvement of third parties in childcare, provided that it does not eliminate the primary responsibility of parents and continues to ensure the welfare of the child. Under Indonesian positive law, daycare practices are allowed as long as they comply with the principles of child protection and the best interests of the child. This study concludes that daycare can be regarded as a legally acceptable form of modern collective childcare, as long as parents remain the primary subjects responsible for the child’s growth and development